Understanding the deposition mechanism burning Fe - rich Zhundong coal in a 0.4 MW pilot-scale facility - Yongqiang Tian; Xiang He; Weizhi Lv; Dafu Ma; Xu Zhao (Fuel Processing Technology, 2025)
This study presents a comprehensive investigation of slagging characteristics associated with Fe-rich Zhundong coal (ZDC) combustion utilizing a 0.4 MWth pilot-scale facility. Slag specimens collected from three critical locations - bottom-of-furnace (BOF), superheater, and reheater zones - were systematically characterized through multi-analytical approaches including X-ray fluorescence (XRF), X-ray diffraction (XRD), and scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDS), complemented by molecular dynamics simulations to elucidate microscopic deposition mechanisms. Key findings reveal that: Distinct melting phenomena were observed across all sampling locations under flue gas temperatures (FGT) ranging from 1000 to 1350 °C, primarily attributed to both the formation of SiCa low-temperature eutectic phases and fluxing effects of Fe-bearing material. Comparative analysis identified sulfate-induced contamination in reheater deposits at moderate-to-low FGT regimes (1000–1200 °C), demonstrating deposition characteristics analogous to Ca-rich ZDC slag formations. The interaction mechanisms of sulfur in reheater zones promoted FeNa synergistic effects. The slag produced through low-temperature ashing exhibits lower fusion temperatures. Molecular dynamics simulations further confirmed that elevated combustion temperatures facilitate SiCa eutectic formation while promoting preferential deposition of Na2SO4/ CaSO4 on low-temperature heat exchange surfaces. When using Fe-rich ZDC in the ∏-type boiler, the FGT at the furnace outlet needs to be reduced to at least 1000 °C.